2019
DOI: 10.1186/s13098-019-0507-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of genistein on lipid levels and LDLR, LXRα and ABCG1 expression in postmenopausal women with hyperlipidemia

Abstract: BackgroundThis study investigates the effect of genistein (Gen) on the lipid profiles and expression of low-density lipoprotein receptor (LDLR), liver X receptor α (LXRα) and ATP-binding cassette transporter G1 (ABCG1) in the plasma macrophages of postmenopausal women with hyperlipidemia in China.MethodsThis study considered 187 cases, where 160 postmenopausal women had hyperlipidemia. The subjects were divided into placebo group (PG) and experimental group (EG). EG received 60 mg/day of Gen, PG received place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Those three isoflavonoids were the possible compound to have hypolipidemic activity through modulating de novo cholesterol biosynthesis. These results supported previous studies which reported that Daidzein, Genistein, and Glycitein could repair blood lipid profile [40][41][42][43] and suggested a new mechanism of hypocholesterolemic activity through the modulation of cholesterol biosynthesis. The inhibition of HMGCR as the rate-limiting factor of cholesterol biosynthesis upregulates LDL Receptor (LDLR) and allows plasma cholesterol uptake to achieve lower blood cholesterol levels [44].…”
Section: Molecular Dynamics Simulationssupporting
confidence: 92%
“…Those three isoflavonoids were the possible compound to have hypolipidemic activity through modulating de novo cholesterol biosynthesis. These results supported previous studies which reported that Daidzein, Genistein, and Glycitein could repair blood lipid profile [40][41][42][43] and suggested a new mechanism of hypocholesterolemic activity through the modulation of cholesterol biosynthesis. The inhibition of HMGCR as the rate-limiting factor of cholesterol biosynthesis upregulates LDL Receptor (LDLR) and allows plasma cholesterol uptake to achieve lower blood cholesterol levels [44].…”
Section: Molecular Dynamics Simulationssupporting
confidence: 92%
“…Additionally, genistein and biochanin A are the main components of D. odorifera leaves [ 27 ]. In the previous reports, genistein had a hypolipidemic effect on menopausal women with hyperlipidemia [ 43 ] and ameliorated dyslipidemia and hepatic steatosis in hyperlipidemic hmsters [ 32 ] and diabetic mice [ 44 ]. Biochanin A mitigates dyslipidemia in hyperlipidemic mice [ 33 ], atherosclerotic mice [ 45 ], and diabetic rats [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peaks 23 and 25 with pseudomolecular ions at m/z: 269.0595 and 431.09843 were devoided as genistein ( C 15 H 10 O 5) and genistein 5-O-glucoside ( C 21 H 20 O 10). Genistein showed lipid lowering effects modulating the plasma lipid indices in women with hyperlipidemias (Zhang & Chi, 2019).…”
Section: Isoflavonesmentioning
confidence: 98%